Pelatihan Dakwah Digital Live Streaming Sebagai Upaya Program Paham Digital Pemuda Desa Bulu Kediri - M Thoriqul Huda; Nur Maria Setyorini; Yulia Lailatul Fitria Wulandari; Umi Masyitoh; Lailatul Rohmah Irfa’ud Darojah; Helmalia Herni Putri Aryuni; Eva Khoirun Ni’mah; Ahmad Faiz Yulianta; Binti Ro’ikatul Jannah; Ayu Fajar Lestari; Selsa Rinwelmina; Nanda Ayu Pransischa; Aan Khunayfi A’ynul Haq; Intan Masnurti Jayanti; Muhammad Fadli Zuhairi; Mohammad Fauzi Rohman (TAAWUN, 2023)
The fact that the development of social media has entered into different facets of life is inevitable. Of course, this can be used well, for example in the dissemination of information or religious proselytizing on social media. Social media digital da'wah training through live streaming is one form of utilizing media as a means of da'wah and an effort to mobilize youth in religious activities and social media publications. This is because Bulu Village is an area where the community is 100% Muslim and has many routine religious activities. In social media digital da'wah training through live streaming, the method used in this community service activity is the PAR (Participatory Action Research) method. The PAR (Participatory Action Research) method is a method that combines research and continuous action by involving the community. By participating in this training, participants can have the initial provisions to do live streaming independently via smartphone or camera. The development of technology is very influential on the method of da'wah so in its implementation, the way of da'wah must be adjusted to technological developments so that it is not left behind and can run effectively.